Ir(iii)-Catalyzed direct C–H functionalization of N-phenylacetamide with α-diazo quinones: a novel strategy for producing 2-hydroxy-2′-amino-1, 2′-biaryl scaffolds. Issue 23 (26th February 2020) - Li, Xingjun; Wang, Jiang; Xie, Xiong; Dai, Wenhao; Han, Xu; Chen, Kaixian; Liu, Hong
Abstract : A novel strategy is reported for the construction of 2-hydroxy-2′-amino-1, 1′-biaryl scaffolds via Ir(iii )-catalyzed direct C–H bond activation under mild reaction conditions. Abstract : α-Diazo quinones were applied in an Ir(iii )-catalyzed direct C–H functionalization assisted by N -phenylacetamide for the construction of highly functionalized 2-hydroxy-2′-amino-1, 1′-biaryl scaffolds in good to excellent yields. This strategy features operational simplicity, atom- and step-economy and high efficiency.